Demand and supply for telematics in the development process : relevance to the sectors of public concern. - MULLER, Jurgen (1995)
Discusses how, within the context of the ongoing technological revolution, access to telematics facilities and services can be improved through cooperative user strategies, partnerships between users and telecommunication operators, and coherent development policies encompassing a wide intersectoral approach.